Inflammatory Myofibroblastic Tumor: A Rare Tumor in the Tongue - Nur Yucel Ekici; Tuba Bayindir; Ahmet Kizilay; Nasuhi Engin Aydin (Case Reports in Otolaryngology)
Inflammatory myofibroblastic tumor is composed of myofibroblast and inflammatory cell infiltration of the tissue. Malign transformation and recurrence rate of this tumor is rare and accepted as benign fibroinflammatory disease. The main etiology is unclear, but infection, trauma, and immunologic event are accused. In this study, we presented a 75-year-old man with a mass on his tongue, which was diagnosed as “inflammatory myofibroblastic tumor.” This type of tumor is rarely seen in the tongue and might be difficult to diagnose. Complete mass excision was provided for an adaquete treatment.